Transformative Psychopharmacology: the Case of 5-Methoxy-N,N-Dimethyltryptamine - M Keppel Hesselink, Jan (International Journal of Psychotherapy Practice and Research, 2019)
Since the 2nd part of last century neo-shamanic rituals using mind-altering extracts from plants or animals have become increasingly popular in Europe and the USA. The first rituals coming to the west were based on drinking a special Amazonian tea, Ayahuasca, based on 2 different plants, with active compounds belonging to the class of the beta-carbolines (harmala alkaloids) and tryptamines. The use of such compounds will be described from the perspective of the transformative psychopharmacology: that part of psychopharmacology studying the use of psychoactive compounds to achieve a new balance, a transformation or healing and sometimes even leading to a cure. Examples of curing are meanwhile well documented, for instance the positive influence on drug abuse and addiction, alcoholism. The importance of the healing aspects of these rituals however are often neglected or overlooked. For users, these are key however. As medicine becomes more and more personalized and postmodern, it will be relevant to understand why patients and healthy people decide to participate in healing rituals based on psycho-active compounds. We will present the pharmacology, the transformative psychopharmacology, the effects and adverse events of 5-methoxy-N, N-dimethyltryptamine (5-MeO-DMT) and its place in postmodern medicine.
Keywords: 5-MeO-DMT; DMT; Ayahuasca; healing; transpersonal; pharmacology; postmodern medicine.